Communication in Pharmacy Practice - Susanne Kaae (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This reprint book 'Communication in Pharmacy Practice' is launched to help improve communication practices by increasing knowledge of different aspects of communication in pharmacy practice. The book consists of recently published research articles and illustrates that pharmacy communication is a research subject that is investigated globally and from many perspectives. The overall pharmacy communicational themes investigated and discussed in this book are as follows: Communication between health care professionals; communication between pharmacists and patients in the context of both prescription and over-the-counter (OTC) medicines; and factors impacting communication. There are many challenges for communication in pharmacy practice today, and several are highlighted in this book. A central conclusion to the research contributions of several of the authors is the specific need to further develop direct, face-to-face communication between pharmacy staff and patients/consumers including tools to better address patient's needs.